Prevalence of schistosomiasis and associated risk factors among residents of Ndikinimeki district, Central Cameroon Region - Mr Bienvenu Balifeli; Ms Laurelle Djieukap Njieyap; Dr Alvine Christelle Kegne Fokam; Mr Fru Chi Tchampo; Pr Chinyere Ukaga; Dr Herman Parfait Awono Parfait; Pr Jeannette Tombi (International Journal of Infectious Diseases)
Introduction: Schistosomiasis is considered one of the most important NTDs in the world. It remains a public health problem in developing countries, with 251.4 million people at high risk. Knowledge surveys, attitudes and practices, and a parasitological study were conducted from June to October 2023 among residents of this locality aged 15 years and over to assess the distribution of intestinal parasitic infections and risk factors in the borough of Ndikinimeki, central region of Cameroon. Parasitological analysis was carried out on stool and urine samples using sedimentation techniques and Kato-Katz and Ritchie. Subsequently, data on sociodemographic status, precautions against intestinal parasitic diseases, and behaviours involving increased exposure to risk environments were documented. Results: Of the 410 participants, 61.57% of whom were female and 38.53% of whom were male—and whose ages ranged from 40.20 years on average, 5.36% had either S. haematobium or S. mansoni infection, whereas 3.01% and 2.76% had S. mansoni and S. haematobium infection, respectively. The parasite species and sociodemographic variables influenced the infection rates and risks of the participants. In general, the risk analysis showed that the following factors were strongly associated with the risk of infection with S. haematobium: frequency of population visits to the watercourse (OR=1.71; IC=0.54-5.87, p=0.365), proximity of the houses to the watercourse (OR=1.25; IC=0.36-3.97, p=0.711), and defecation and urination in the watercourses (OR = 3.45; CI = 0.66-63.45, p = 0.239). Except for S. mansoni, there are other factors that are more important than sex (OR=1.34; CI=0.38–4.52, p=0.634), age (OR=1.05; CI=0.24–4.52, p=0.946), and time spent in a stream (OR=2.89; CI=0.47–22.43, p=0.253), which also have an impact on the risk of infection. Depending on the time spent in the stream, the risk of S. mansoni infection was high in people who spent 3 hours more in the stream. Discussion: The lack of drinking water in this locality pushes people to use surface water for their domestic activities. This would contribute to an infestation risk. Time spent in these infested streams would make schistosomiasis infestations possible. Conclusion: This study demonstrates that this locality is a coendemic risk zone for urinary and intestinal schistosomiasis. This calls not only for the mobilization of the government but also for the participation of the populations of this area in the control, prevention, and eradication of the disease. It is therefore important to focus on raising awareness and strengthening the preventive measures already put in place to prevent infestation and stop the transmission of schistosomiasis in this locality.